The Alfonso Coffee+cacao Central a production, development, and marketing complex - Leyran, Jeromira Luz V. (College of Architecture, University of the Philippines Diliman, 2020)
The project's main agenda of security -- providing a certain degree of certainty by transcending the inevitability of urbanization -- serves as the driving force of the study. As Alfonso, Cavite is in state of uncertainty -- an agricultural town in the threat of rapidly transforming and acclimating to an urbanized setting, yet at the same time unready and struggling to keep up with this speedy change -- the agenda of security encompasses the need of a solution for the uncertain situation of the agriculture industry of Alfonso. Through this agenda, architecture can provide the means to transcend the impending urbanization of Alfonso by tapping into the underutilized potential of agriculture -- specifically, its coffee and cocoa industry, by creating spaces that provide support and showcase the process involved in coffee and cocoa from the tree to the table, and is distinctive of Alfonso's agricultural heritage and character. the ALFONSO COFFEE + CACAO CENTRAL provides a solution to the urban problem faced by the locale by providing spaces for production, development, and marketing Alfonso's coffee and cacao products. The design vision for this spatial intervention is to create a visible, continuous, and experiential structure -- a "visible" space that sparks recognition of a ubiquitous product yet somehow unique to the locale, and at the same time a continuous structure in the sense that circulation and spaces are efficient, all the while providing a sensorial experience to all of its users. By focusing on honing and leveraging existing strengths -- the coffee and cocoa industry -- within the Alfonso, it would be able to provide a solution to urban problem that exist within the locale.